2011
DOI: 10.1038/nn.2800
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical chemosensory regulation of male-male social interactions in Drosophila

Abstract: Pheromones regulate male social behaviors in Drosophila, but the identities and behavioral role(s) of these chemosensory signals, and how they interact, are incompletely understood. Here we show that (Z)-7-tricosene (7-T), a male-enriched cuticular hydrocarbon (CH) previously shown to inhibit male-male courtship, is also essential for normal levels of aggression. The opposite influences of 7-T on aggression and courtship are independent, but both require the gustatory receptor Gr32a. Surprisingly, sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
219
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(231 citation statements)
references
References 50 publications
12
219
0
Order By: Relevance
“…Among the Grs observed to express in neurons apparently innervating the reproductive organs, Gr32a is required for pheromone detection (Miyamoto and Amrein, 2008;Wang et al, 2011), and Gr64c is a member of the putative sugar receptor subfamily . It is as yet unclear whether these Grs act as chemosensors for certain molecules in the reproductive organs, or if they act as sensors for completely different modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Among the Grs observed to express in neurons apparently innervating the reproductive organs, Gr32a is required for pheromone detection (Miyamoto and Amrein, 2008;Wang et al, 2011), and Gr64c is a member of the putative sugar receptor subfamily . It is as yet unclear whether these Grs act as chemosensors for certain molecules in the reproductive organs, or if they act as sensors for completely different modalities.…”
Section: Discussionmentioning
confidence: 99%
“…1F). Furthermore, in an Or47b mutant (22), which has two identical independent knockout alleles, Or47b [2] and Or47b [3] (in all experiments, we used only Or47b [3] after backcrossing it to the Canton-S background to minimize genetic background effects), the responses of at4A OSNs to ML were completely abolished, whereas at4C OSNs still responded to the three fly odorants ( Fig. 1 H and I).…”
Section: Significancementioning
confidence: 99%
“…The elucidation of the genes and neuronal circuitry that regulate aggression is key to the understanding of its mechanisms. The fruit fly Drosophila melanogaster has recently emerged as a model system to study aggression [2][3][4][5][6][7][8][9][10][11][12] . Several conserved neuromodulators have been shown to play a role in fly aggression [5][6][7] .…”
mentioning
confidence: 99%
“…For example, serotonin plays a critical role in the modulation of aggression across a broad range of species but the effect is different in vertebrates and invertebrates 13,14 . In addition, fly-specific pheromonal cues have been identified that affect aggression in Drosophila [10][11][12] . What remains unclear is whether the molecular mechanisms that control aggression in flies are mechanistically conserved with those in mammals.…”
mentioning
confidence: 99%